Rejecting Limits and Opening Possibilities in the Works of Iain Banks - Roebuck, Olga (Univerzita Pardubice, 2016)
This text deals with the question of Scottish self-definition and also the escape from it. Scottish identity debate in 1980s and 1990s took on different forms and searched for other inspirations: outside Scotland or in dealing with identities traditionally overlooked due to the overall focus on national identity. This paper thus analyses the question of Scottishness through the subversive voice addressing the identities traditionally problematic in Scotland or even through individual self-definition as presented in Iain Banks´s novels The Wasp Factory and The Crow Road.
Odmítání hranic a otevírání možností v dílech Iana Bankse
Keywords: Scotland; cultural subversion; Scottishness; Ian Banks; The Wasp Factory; The Crow Road; Skotsko; kulturní subverze; skotská identita; Ian Banks; Vosí továrna; Vraní ulice